Effects of Etamsylate on Platelet Functions and Arachidonic Acid Metabolism - Okuma, M; Takayama, H; Sugiyama, T; Sensaki, S; Uchino, H (Thrombosis and Haemostasis, 1982)
The effects of etamsylate on human platelet aggregation and ATP release as well as on the arachidonate metabolism by the platelet have been studied. Etamsylate enhanced these platelet functions induced by arachidonic add (AA), thromboxane A2, collagen and caldum ionophore A23187 but not those induced by ADP and epinephrine. In experiments with cyclooxygenase-inhibited platelets, AA-induced platelet aggregation was completely inhibited and it was not enhanced by etamsylate, while A23187-induced aggregation was partially inhibited and this aggregation was enhanced by etamsylate. Platelet AA metabolism including thrombin-induced AA liberation from phospholipids as well as the lipoxygenase and cyclo-oxygenase pathways was not significantly affected by etamsylate. These results suggested that etamsylate enhanced platelet response to thromboxane A2 and calcium ionophore and that this could be included as a mechanism for its potentiating effect on platelet functions.
Keywords: Etamsylate; Platelet function; Arachidonic add metabolism; Thromboxane A2; Calcium ionophore